Economic soundness and Psychological Well-being among the Elderly - Rani, Kavitha; Revanth, R.; Shanmughavadivu, N.; Lovelina Little Flower, F.X. (South Asian Journal of Social Sciences and Humanities, 2023)
Mental Health is the overall concern for many throughout the world, it helps the individual to express their feelings and engage with others. To achieve a stable or positive mental health, one should achieve a positive well-being. Well-being could be viewed with different components, among them psychological well-being is a main factor, which is debatable. Psychological well-being of an individual depends on his interaction with himself and the society. Many researches have been carried out to find the relationship between various factors and individuals psychological well-being. Elderly termed to be the most vulnerable population in terms of mental health issues, as they face lot of problems related to health, economic stability and difficulties in coping with the modern world. Individuals over 60 years are referred to as elderly (WHO, 2019), their population is one billion and is projected to reach 2.1 billion by 2050 around the world. The Mental health services in India are not standardized to satisfy the elderly needs. India with 1.3 billion populations among which 27% are youth, in near future the elderly population is going to be high in India. It is the need of the hour to direct these youth population towards a positive elderly life. Thus, this study focuses on analysing the impact of the saving habit and the expenditure of elderly in determining their psychological well-being. For this empirical study, descriptive design using purposive sampling was adopted. The researcher has collected data from elderly population living in Tauta Nagar, Thondamuthur Road, Coimbatore and used the psychological well-being scale. The results of the study showed  monthly income and savings of the elderly positively influence the psychological well-being. Whereas, monthly expenditure on the other hand doesn’t show any influence when kept as a predictor variable.
Keywords: Economic Soundness; Mental Health; Elderly; Psychological Well-being; Financial planning and management